Towards a modular theory of trophic interactions. (12th November 2021) - Wootton, Kate L.; Curtsdotter, Alva; Roslin, Tomas; Bommarco, Riccardo; Jonsson, Tomas
Abstract: Species traits and environmental conditions determine the occurrence and strength of trophic interactions. If we understand the relationship between these factors and trophic interactions, we can make more accurate predictions and build better trophic‐interaction models. We can compare traits and conditions by considering their effect on different parts (steps) of a trophic interaction, such as the steps search and pursuit . By linking traits to relevant steps, we can use these relationships to build trophic‐interaction models. Currently, this is done ad hoc, defining steps based on the species and traits of interest. This makes it difficult to compare across traits and species and gain an overarching understanding of how traits and the environment drive trophic interactions. We present a comprehensive approach for the explicit choice of interaction steps and species traits or environmental conditions, which is readily integrated into existing models. The core of this framework is that it is modular; we present eight steps that occur in all trophic interactions and use them to build a modular, general dynamic model. When applying the framework, one explicitly selects only the most relevant steps and uses those to build a specific model. To build our modular framework, we revisit and expand the functional and numerical response functions, dividing the trophic interaction into eight steps: (1) search, (2) prey detection, (3) attack decision, (4) pursuit, (5) subjugation, (6) ingestion, (7) digestion and (8) nutrient allocation. Together these steps form a general dynamical model where trophic interactions can be explicitly parameterized for multiple traits and environmental factors. We then concretize this approach by outlining how a specific community can be modelled by selecting key modules (steps) and parameterizing them for relevant factors. This we exemplify for a community of terrestrial arthropods using empirical data on body size and temperature responses. With species interactions at the core of community dynamics, our modular approach allows for quantification and comparisons of the importance of different steps, traits, and abiotic factors across ecosystems and trophic‐interaction types, and provides a powerful tool for trait‐based prediction of food‐web structure and dynamics. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.